2003
DOI: 10.31887/dcns.2003.5.3/aallen
|View full text |Cite
|
Sign up to set email alerts
|

Obsessive-compulsive spectrum disorders

Abstract: The obsessive-compulsive spectrum is an important concept referring to a number of disorders drawn from several diagnostic categories that share core obsessive-compulsive features. These disorders can be grouped by the focus of their symptoms: bodily preoccupation, impulse control, or neurological disorders. Although the disorders are clearly distinct from one another, they have intriguing similarities in phenomenology, etiology, pathophysiology, patient characteristics, and treatment response. In combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 114 publications
1
11
0
1
Order By: Relevance
“…However, individuals with these obsessive-compulsive disorder (OCD) exhibit repetitive behaviors because they have a defect in the mechanism that enables them to inhibit acting. [ 26 ] This was confirmed in the current study, which found that students with a lower academic % had a higher CSS score.…”
Section: Discussionsupporting
confidence: 84%
“…However, individuals with these obsessive-compulsive disorder (OCD) exhibit repetitive behaviors because they have a defect in the mechanism that enables them to inhibit acting. [ 26 ] This was confirmed in the current study, which found that students with a lower academic % had a higher CSS score.…”
Section: Discussionsupporting
confidence: 84%
“…In addictive behaviors, impulsivity has been recognized as a relevant risk factor for (early) substance use initiation (e.g., the transition from the naïve condition to recreational use and from recreational use to abuse and dependence), for persistence of use (e.g., drugs may harm the cognitive systems that control behavior) and for relapse (e.g., suppressing behavioral control over positive reinforcing behaviors) (16,17). Although not planned, impulsive behavior is driven by the promise of reward (positive reinforcement).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, we suggest that OCD and ADHD may not be two independent conditions, but in many aspects rather two poles of a common dimension. We are not the first to consider this possibility, as other authors have already suggested that OCD and ADHD might fall onto an impulsive-compulsive continuum (Allen et al, 2003). This continuum has been characterized in terms of harm avoidance at the compulsive pole and as risk seeking at the impulsive pole (Allen et al, 2003).…”
Section: Co-existence Of Ocd and Adhdmentioning
confidence: 91%